Isolation and maintenance-free culture of contractile myotubes from Manduca sexta embryos. - Amanda L Baryshyan (Public Library of Science (PLoS), 2012)
Skeletal muscle tissue engineering has the potential to treat tissue loss and degenerative diseases. However, these systems are also applicable for a variety of devices where actuation is needed, such as microelectromechanical systems (MEMS) and robotics. Most current efforts to generate muscle bioactuators are focused on using mammalian cells, which require exacting conditions for survival and function. In contrast, invertebrate cells are more environmentally robust, metabolically adaptable and relatively autonomous. Our hypothesis is that the use of invertebrate muscle cells will obviate many of the limitations encountered when mammalian cells are used for bioactuation. We focus on the tobacco hornworm, Manduca sexta, due to its easy availability, large size and well-characterized muscle contractile properties. Using isolated embryonic cells, we have developed culture conditions to grow and characterize contractile M. sexta muscles. The insect hormone 20-hydroxyecdysone was used to induce differentiation in the system, resulting in cells that stained positive for myosin, contract spontaneously for the duration of the culture, and do not require media changes over periods of more than a month. These cells proliferate under normal conditions, but the application of juvenile hormone induced further proliferation and inhibited differentiation. Cellular metabolism under normal and low glucose conditions was compared for C2C12 mouse and M. sexta myoblast cells. While differentiated C2C12 cells consumed glucose and produced lactate over one week as expected, M. sexta muscle did not consume significant glucose, and lactate production exceeded mammalian muscle production on a per cell basis. Contractile properties were evaluated using index of movement analysis, which demonstrated the potential of these cells to perform mechanical work. The ability of cultured M. sexta muscle to continuously function at ambient conditions without medium replenishment, combined with the interesting metabolic properties, suggests that this cell source is a promising candidate for further investigation toward bioactuator applications.